Verification and Pre-commercial testing of european corn borer and gibberella ear rot resistant varieties - Hamilton, R.I.=700 1 Reid, L.M.; Meloche, F.
Sumario (En)
Ilus.; 12 ref.
Keywords: RESISTENCIA A LAS PLAGAS; RESISTENCIA A LA ENFERMEDAD; VARIEDADES; PODREDUMBRES; GIBBERELLA; FUSARIUM; OSTRINIA NUBILALIS; VARIACION GENETICA